Genomewide transcriptional reprogramming in the seagrass Cymodocea nodosa under experimental ocean acidification. Issue 16 (10th July 2017) - Ruocco, Miriam; Musacchia, Francesco; Olivé, Irene; Costa, Monya M.; Barrote, Isabel; Santos, Rui; Sanges, Remo; Procaccini, Gabriele; Silva, João
Abstract: Here, we report the first use of massive‐scale RNA‐sequencing to explore seagrass response to CO2 ‐driven ocean acidification (OA). Large‐scale gene expression changes in the seagrass Cymodocea nodosa occurred at CO2 levels projected by the end of the century. C. nodosa transcriptome was obtained using Illumina RNA‐Seq technology and de novo assembly, and differential gene expression was explored in plants exposed to short‐term high CO2 /low pH conditions. At high p CO2, there was a significant increased expression of transcripts associated with photosynthesis, including light reaction functions and CO2 fixation, and also to respiratory pathways, specifically for enzymes involved in glycolysis, in the tricarboxylic acid cycle and in the energy metabolism of the mitochondrial electron transport. The upregulation of respiratory metabolism is probably supported by the increased availability of photosynthates and increased energy demand for biosynthesis and stress‐related processes under elevated CO2 and low pH. The upregulation of several chaperones resembling heat stress‐induced changes in gene expression highlighted the positive role these proteins play in tolerance to intracellular acid stress in seagrasses. OA further modifies C. nodosa secondary metabolism inducing the transcription of enzymes related to biosynthesis of carbon‐based secondary compounds, in particular the synthesis of polyphenols and isoprenoid compounds that have a variety of biological functions including plant defence. By demonstrating which physiological processes are most sensitive to OA, this research provides a major advance in the understanding of seagrass metabolism in the context of altered seawater chemistry from global climate change.